Blog de periodismo de viajes, una estrategia para promover el turismo en la provincia de El Oro - Torres Quevedo, Abigaíl Mariela (Machala, 2020)
TRAVEL JOURNALISM BLOG: A STRATEGY TO PROMOTE TOURISM IN EL ORO PROVINCE Author: Abigail Mariela Torres Quevedo Tutor: Diana Viveros Aguilar The present investigation aims to promote the tourist attractions of the province of El Oro, located in the south of Ecuador in a geographical area known as the coastal region, directing this new branch of journalism that has been used as strategies to enhance the tourist attractions of a certain place, using the traditional or digital media that are in vogue today, In this way we also sought to determine the types of sectors that need to be promoted in the province, a point that was established thanks to the dialogue with experts related to the subject in the tourism sector of the province, through in-depth interviews, which allowed us to understand that thanks to the fact that the province of El Oro has several climatic floors, it is fortunate to show itself to tourists by presenting different options when visiting it. In this context of the research, a content analysis was also carried out which consisted in identifying their writing style, their web content (photos, text and videos), the periodicity of their publications, their interaction with their followers and the types of digital platforms they use. The objective was to find out what characterized each of the different blogs selected. In order to reach several people showing the beauty of the province through the travel reports, a blog was created, a digital platform whose content is mixed (photos, text, video) which reveals in a first edition the beauty of the Archipelago of Jambelí taking as a starting point Jambelí Island which is shown through photographs part of the island as its species, its typical dishes and characters of the island and also the extreme sports that can be performed there when visiting it. Through a small video you can also visualize part of the mangrove area that can be observed on the way to the island. Also, thanks to the techniques applied in this investigation, a significant contribution was made to meet the main objective: to create a blog on travel journalism through the development of strategies to promote tourism in the province of El Oro. In the last decades this specialization of journalism has been gaining ground as a very useful information tool so that through experiences getting to know other cultures, seeing new landscapes and sharing anecdotes with locals, others are inspired to leave their comfort zone and visit these places and thus spread information about this province using a digital platform embodied in a travel blog. Showing from archaeological ruins, orchid trails, forests, magical villages and a beautiful archipelago surrounded by several islands. The tourist resources of this province have a natural, historical and cultural value, this blog was well accepted in which the focus group was very interested in knowing what would be the next places to visit to see them through the blog and take notes when visiting some corner of the province of El Oro
BLOG DE PERIODISMO DE VIAJES: UNA ESTRATEGIA PARA PROMOVER EL TURISMO EN LA PROVINCIA DE EL ORO Autora: Abigail Mariela Torres Quevedo Tutora: Lcda. Diana Viveros Aguilar El presente trabajo de investigación pretende promover los atractivos turísticos de la provincia de El Oro ubicada al sur del Ecuador en una zona geográfica conocida como región litoral o costa, dirigiendo esta nueva rama del periodismo que se la viene utilizando como estrategias para potencializar atractivos turísticos de cierto lugar, empleando los medios tradicionales o digitales que hoy están en boga, así también se buscó determinar los tipos de sectores que se necesita promocionar en la provincia, punto que pudo ser establecido gracias al diálogo con expertos relacionados al tema en el sector turístico de la provincia, mediante entrevistas a profundidad, lo que permitió comprender que gracias a que la provincia de El Oro cuenta con varios pisos climáticos la hace afortunada de mostrarse a los turistas presentando diferentes opciones a la hora de visitarla. En este contexto de la investigación también se realizó un análisis de contenido que consistió en identificar su estilo de redacción, su contenido web (fotos, texto y videos), periodicidad de sus publicaciones, interacción con sus seguidores y tipos de plataformas digitales que utilizan. Con el objetivo de saber qué los caracteriza a cada uno de los diferentes blogs seleccionados. Con la finalidad de llegar a varias personas mostrando la belleza de la provincia mediante las crónicas de viaje, se elaboró un blog, una plataforma digital cuyo contenido es mixto (fotos,texto,video) donde se revela en una primera edición la belleza del Archipiélago de Jambelí tomando como punto de partida la Isla Jambelí la cual se muestra mediante fotografías parte de la isla como sus especies, sus platos típicos y personajes de la isla y así también los deportes extremos que se puede realizar en ella a la hora de visitarla. Por medio de un pequeño video también se logra visualizar parte de la zona de manglar que se puede observar en el trayecto hacia la isla. Así también gracias a las técnicas aplicadas en esta investigación se contribuyo significativamente a cumplir el objetivo principal: Elaborar un blog sobre periodismo de viaje a través del desarrollo de estrategias para promover el turismo en la provincia de El Oro. Ya que en las últimas décadas esta especialización del periodismo ha ido ganando terreno, como una herramienta de información muy útil para que a través de experiencias conociendo otras culturas, viendo nuevos paisajes y compartiendo anécdotas con lugareños, se inspire a otros a salir de su zona de confort y que visiten dichos lugares y así se difunda información de esta provincia haciendo uso de una plataforma digital plasmada en un blog de viajes. Mostrando desde ruinas arqueológicas, senderos de orquídeas, bosques, pueblos mágicos y un lindo archipiélago rodeado por varias islas. Los recursos turísticos de esta provincia poseen un valor natural, historio y cultural, dicho blog tuvo una buena aceptación en la cual el focus grupo se mostró muy interesado en conocer cuáles serían los siguientes lugares que se visitaría para poder verlos a través del blog y tomar notas a la hora de visitar algún rincón de la provincia de El Oro
Keywords: PERIODISMO DE VIAJE; TURISMO; ISLA JAMBELI